Evaluation of crack relief layer for airport runways - Ahmad Zaini, Ashraf (2016)
This paper investigates some observations that have been made in a number of countries around the world on the behavior and function of crack relief layer (CRL). Throughout the years, crack in pavement is a major problem that causes an obstruction to transportation system which has cost multi-millions of dollars. This is especially in airport runway business industry where the air traffic flow of aircraft cannot be easily diverted or disturbed as it involve many parties and would jeopardize a lot of money at stake. This paper describes and investigates the significant and effectiveness of applying CRL into the pavement which will be evaluated to relieve crack. The characteristic of the CRL will be thoroughly investigated to achieve it desirable functional capability to act as the crack relieving layer. The objectives of the experimental study are to identify the optimum bitumen content (OBC) and evaluate the engineering properties of the CRL by using 60-70 PEN bitumen with variation in percentages of bitumen content which are 2.0, 2.5, 3.0, 3.0, and 4.0%. The specimens are mixed and compacted for 50 blows each side and tested. The result shows that the OBC for CRL is 3.0% and the properties of CRL to mitigate crack is distinctly influent by resilient modulus and bulk density values.